Palma forrageira (Opuntia ficus indica e Nopalea cochenillifera) como matéria-prima para produção de etanol celulósico e enzimas celulolíticas - Souza Filho, Pedro Ferreira de (2014)
The need for new sources of energy and the concern about the environment have pushed the search for renewable energy sources such as ethanol. The use of lignocellulosic biomass as substrate appears as an important alternative because of the abundance of this raw material and for it does not compete with food production. However, the process still meets difficulties of implementation, including the cost for production of enzymes that degrade cellulose to fermentable sugars. The aim of this study was to evaluate the behavior of the species of cactus pear Opuntia ficus indica and Nopalea cochenillifera, commonly found in northeastern Brazil, as raw materials for the production of: 1) cellulosic ethanol by simultaneous saccharification and fermentation (SSF) process, using two different strains of Saccharomyces cerevisiae (PE-2 and LNF CA-11), and 2) cellulolytic enzymes by semi-solid state fermentation (SSSF) using the filamentous fungus Penicillium chrysogenum. Before alcoholic fermentation process, the material was conditioned and pretreated by three different strategies: alkaline hydrogen peroxide, alkaline using NaOH and acid using H2SO4 followed by alkaline delignification with NaOH. Analysis of composition, crystallinity and enzymatic digestibility were carried out with the material before and after pretreatment. In addition, scanning electron microscopy images were used to compare qualitatively the material and observe the effects of pretreatments. An experimental design 2² with triplicate at the central point was used to evaluate the influence of temperature (30, 40 and 45 °C) and the initial charge of substrate (3, 4 and 5% cellulose) in the SSF process using the material obtained through the best condition and testing both strains of S. cerevisiae, one of them flocculent (LNF CA-11). For cellulase production, the filamentous fungus P. chrysogenum was tested with N. cochenillifera in the raw condition (without pretreatment) and pretrated hydrothermically, varying the pH of the fermentative medium (3, 5 and 7). The characterization of cactus pear resulted in 31.55% cellulose, 17.12% hemicellulose and 10.25% lignin for N. cochenillifera and 34.86% cellulose, 19.97% hemicellulose and 15.72% lignin for O. ficus indica. It has also been determined, to N. cochenillifera and O. ficus indica, the content of pectin (5.44% and 5.55% of calcium pectate, respectively), extractives (26.90% and 9.69%, respectively) and ashes (5.40% and 5.95%). Pretreatment using alkaline hydrogen peroxide resulted in the best cellulose recovery results (86.16% for N. cochenillifera and 93.59% for O. ficus indica) and delignification (48.79% and 23.84% for N. cochenillifera and O. ficus indica, respectively). This pretreatment was also the only one which did not increase the crystallinity index of the samples, in the case of O. ficus indica. However, when analyzing the enzymatic digestibility of cellulose, alkali pretreatment was the one which showed the best yields and therefore it was chosen for the tests in SSF. The experiments showed higher yield of conversion of cellulose to ethanol by PE-2 strain using the pretreated N. cochenillifera (93.81%) at 40 °C using 4% initial charge of cellulose. N. cochenillifera gave better yields than O. ficus indica and PE-2 strain showed better performance than CA-11. N. cochenillifera proved to be a substrate that can be used in the SSSF for enzymes production, reaching values of 1.00 U/g of CMCase and 0.85 FPU/g. The pretreatment was not effective to increase the enzymatic activity values